World Economy Summer 2024: Growth remains subdued - Klaus-Jürgen Gern; Stefan Kooths; Wan-hsin Liu; Jan Reents; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The global economy has expanded at a moderate pace so far this year. Meanwhile, the previously pronounced differences in economic momentum have diminished, particularly in the advanced economies. While the robust expansion in the United States lost momentum, the economy in Europe picked up noticeably after a period of stagnation. At the same time, there are signs of accelerating production in China, although many indicators suggest that domestic private demand continues to be sluggish. Against this backdrop, growth in world trade in goods resumed. The moderate global economic expansion is likely to continue in the forecast period, with private consumption picking up in Europe as real wages rise again. Next year, the gradual easing of monetary policy should increasingly lend support. All in all, we expect global production - measured on a purchasing power parity basis - to increase by 3.2 percent this and next year, respectively. We raise our forecast for 2024 by 0.4 percentage points compared to our March forecast, while the forecast for 2025 remains unchanged. Although unemployment in the advanced economies will slightly increase this year, it remains at a historically low level. Inflation has barely fallen further recently, mainly due to a stubborn rise in prices for services. The expected further decline towards the target of 2 percent is likely to be slow, and the risk has increased that monetary policy will have to remain restrictive for longer than previously expected. Further risks for the global economy are primarily of a geopolitical nature and arise not least from the uncertainties related to the US presidential elections. An escalation of trade conflicts, for example, would weigh on global economic activity.
Keywords: 330